KAJIAN MENGENAI PENERIMAAN SISTEM INFORMASI WEB PADAMU NEGERI TERHADAP PENDIDIK DAN TENAGA KEPENDIDIKAN DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Ai Umamah (Jurnal Accounting Information System (AIMS), 2018)
Islamic Foundation Nuurul Muttaqiin ia a private school in the Garut which is engaged in Islamic education. Charging administration teachers online or Web Padamu Negeri is an information system that is in use at the Islamic Foundation Nuurul Muttaqiin Cisurupan Garut. With the web Padamu Negeri online expect to help filling teacher administration. Charging a good data teacher is needed in order to facilitate schools and teachers to find information. In support of online data entry Padamu Negeri need support of State Information Systems and Technology quality information. The theory used in this research is the theory butterfly Behaviour Information Systems. This research method using a survey approach and the kind of research is quantitative descriptive. Data collection techniques with interviews, circulate a list of questions and study documentation. Data analysis model used amos 22 version.The population in this study were teachers in the Islamic Foundation Nuurul Muttaqiin Cisurupan Garut registered active in the web information system Padamu Negeri.Total population is 112 people and the number of samples in the meticulous 103 people. The research hypothesis testing with SEM analysis (Structural Equation Model). SEM is a statistical analysis tools in use to complete multilevel research model simultaneously. From the seven proposed hypothesis shows that there are two hypotheses are not supported. First, the Behavioral Intention to use with Actual technology use in the feel of teachers and there is no real relationship (significant). Secondly, it was felt teachers and no real relationship (significant) between the Perceived usefulness Perceived ease of use.